The Concept of ''Disability'' in Architecture as a Power and Ideology Problem - Selma Saltoğlu; Aysun Aydın Öksüz (Iconarp International Journal of Architecture and Planning, 2016)
The concept of disability, which is well accepted around the world and seem to be a statement of positive discrimination at first, requires to become a current issue as an equality problem in architecture and society today. In fact, the definition of disability and its intellectual basis are major and still invisibile obstacles to obtain equal rights for everyone regarding architectural accessibility and participation in social life.